PENGELOLAAN SARANA DAN PRASARANA PRAKTIK PADA JURUSAN TATA BUSANA - Kinder Sihotang; Rohiat Rohiat; Manap Somantrim (UNIVERSITAS BENGKULU, 2017)
The puspose of this research is to describe the management of infrastructure practice in the dressmaking departement at SMK Negeri 3 Bengkulu City” Consists of planning, procurement, inventory, storage, use, maintance and removal. This study used descriptive qualitative approach, and the respondents were the principle, vice principle of infrastructure affarirs, staf facilities and infrastructure, and productive teachers of dressmaking departement. The techniques of data collection used interview, observation and documentation. The result show the management of the practicing facilities of dressmaking departement of secondary at SMK Negeri 3 Bengkulu City was conducated in accordance with applicable regulatons, but there are some aspect of management that are not implemented.